Force Analysis of a Single Grain Cutting Process in Wood Grinding Using Spherical Corundum - Sergey A. Voinash; Alexander V. Sergeevichev; Viktoriia A. Sokolova; Аnna Е. Mikhailova; Еvgeniya О. Ovcharova (Лесной журнал, 2023)
The productivity of the wood grinding process can be increased by using abrasive wheels with spherical corundum grains. They also expand the area of application of rigid abrasive instruments by reducing soiling and eliminating burns on the treated surface. The studies revealed several advantages of the abrasive wheels over sanding paper: very precise processing, achievement of the desired grade of the treated surface, high durability of the instrument, and low cost. A force analysis of a grinding surface with micro-cuttings made of spherical corundum grains was performed depending on the degree of its wear. The results revealed that chip removal by the spherical corundum grains was possible only under certain conditions when the cutting edges of the grains were exposed. Besides, the theoretical dependencies of forces in micro-cutting were obtained from every principal condition for the process of grinding wood and wooden materials: properties of the spheres, treatment modes, and material-related factors. The special properties were analyzed by the chip formation process and self-sharpening conditions of the spherical corundum wheels. The grain size had the greatest influence on the thickness of chips which were cut by one grain. The grain content and bonding, like other properties of the internal volumetric structure, had a less substantial impact. The abrasive tool characteristics must complement the processed material, such as grain size, hardness, and structure. On the other hand, spherical corundum has optimal physical and mechanical properties for grinding, particularly the thickness of the grain’s edges, which primarily determine the material’s tensile strength. The grinding depth and feed rate mostly define the parameters of the grinding performance of wood and wood-based materials. An increase in those leads to a rise in cutting forces, roughness of the ground surface, a reduction in the grinding length over the period of the wheel’s durability, and the grinding coefficient. If the grinding depth and feed rate are constant, the performance can be improved by increasing the cutting rate. For citation: Sergeevichev A.V., Sokolova V.A., Mikhailova A.E., Ovcharova E.O., Voinash S.A. Force Analysis of a Single Grain Cutting Process in Wood Grinding Using Spherical Corundum. Lesnoy Zhurnal = Russian Forestry Journal, 2023, no. 3, pp. 140–154. (In Russ.). https://doi.org/10.37482/0536-1036-2023-3-140-154